2020
DOI: 10.1051/0004-6361/202039085
|View full text |Cite
|
Sign up to set email alerts
|

Sustained oscillations in interstellar chemistry models

Abstract: Context. Nonlinear behavior in interstellar chemical models has been recognized for 25 years now. Different mechanisms account for the possibility of multiple fixed-points at steady-state, characterized by the ionization degree of the gas. Aims. Chemical oscillations are also a natural behavior of nonlinear chemical models. We study under which conditions spontaneous sustained chemical oscillations are possible, and what kind of bifurcations lead to, or quench, the occurrence of such oscillations. Methods. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…The actual gas phase abundances of CO versus time for these models are shown in Figure 3c, along with similar evolutions of HCO + and N 2 H + . In this figure, we sometimes see oscillations in the abundances of CO, HCO + and N 2 H + , i.e., in the models with high CRIR and where the condition 10 18 cm −3 s < n H /ζ < 2.2 × 10 18 cm −3 s. Such behaviour has been noted in the previous study of Maffucci et al (2018), corresponding to the High Ionization Phase (HIP) case discussed by Roueff & Le Bourlot (2020). More generally, the results of Figures 1c and 2c indicate that as ζ increases, CO depletion begins earlier in time, but reaches a lower equilibrium value.…”
Section: Dependence On Cosmic Ray Ionization Ratesupporting
confidence: 74%
“…The actual gas phase abundances of CO versus time for these models are shown in Figure 3c, along with similar evolutions of HCO + and N 2 H + . In this figure, we sometimes see oscillations in the abundances of CO, HCO + and N 2 H + , i.e., in the models with high CRIR and where the condition 10 18 cm −3 s < n H /ζ < 2.2 × 10 18 cm −3 s. Such behaviour has been noted in the previous study of Maffucci et al (2018), corresponding to the High Ionization Phase (HIP) case discussed by Roueff & Le Bourlot (2020). More generally, the results of Figures 1c and 2c indicate that as ζ increases, CO depletion begins earlier in time, but reaches a lower equilibrium value.…”
Section: Dependence On Cosmic Ray Ionization Ratesupporting
confidence: 74%
“…The ice chemistry can reasonably well be approximated with a stationary chemistry for A V ≲ 5 − 10 and even deeper in the cloud for some ice species, such as J(CO) (see also Hollenbach et al 2009). On the other hand, time-dependent computations by Esplugues et al (2019) show that J(H 2 O) abun-dance at strong FUV illumination and n = 10 5 cm −3 reaches a plateau at A V > 7 after 10 6 −10 7 yr. We note that previous studies showed the existence of multiple chemical solutions (Le Bourlot et al 1993bBourlot et al , 1995Lee et al 1998;Charnley & Markwick 2003;Boger & Sternberg 2006;Dufour & Charnley 2019) as well as the existence of sustained chemical oscillations (Roueff & Le Bourlot 2020) in gas-phase models of the ISM.…”
Section: Chemical Time Scalesmentioning
confidence: 48%
“…On the other hand, time-dependent computations by Esplugues et al (2019) show that J(H 2 O) abundance at strong FUV illumination and n = 10 5 cm −3 reaches a plateau at A V > 7 after 10 6 − 10 7 yr. Note, that previous studies showed the existence of multiple chemical solutions (Le Bourlot et al 1993bBourlot et al , 1995Lee et al 1998;Charnley & Markwick 2003;Boger & Sternberg 2006;Dufour & Charnley 2019) as well as the existence of sustained chemical oscillations (Roueff & Le Bourlot 2020) in gas-phase models of the ISM.…”
Section: Chemical Time Scalesmentioning
confidence: 87%